Interspecific comparison of radiocesium trophic transfer in two tropical fish species. (September 2018) - Pouil, Simon; Teyssié, Jean-Louis; Fowler, Scott W.; Metian, Marc; Warnau, Michel
Abstract: The trophic transfer of radiocesium ( 134 Cs) was investigated in two tropical fish, the silver moony Monodactylus argenteus and the spotted scat Scatophagus argus . Juveniles of both species were exposed to dietary 134 Cs using the pulse-chase feeding methodology. The food was brine shrimp ( Artemia salina ) previously exposed to the dissolved radiotracer. Depuration kinetics of 134 Cs were followed for 45 d. Results showed that Cs was similarly efficiently assimilated by both species (AE > 50%). The estimated trophic transfer factors in the two species ranked from 1 to 2, suggesting that 134 Cs could be biomagnified in both omnivorous species. In complement, dissections of 7 body compartments were carried out at three different times in order to highlight 134 Cs organotropism. 134 Cs organotropism was similar in both species: more than 50% of 134 Cs was quickly distributed in the muscles and skeleton (after 3 days of depuration), which is likely related to the analogous behavior between Cs and K, an essential element for muscle contractions and bone formation. Highlights: Radiocesium was efficiently and similarly assimilated by the two fish species. Results suggested that radiocesium could be biomagnified in omnivorous species. Up to 70% of the radiocesium was distributed in the muscles and skeleton.